2011
DOI: 10.1007/s00468-011-0660-9
|View full text |Cite
|
Sign up to set email alerts
|

European pome fruit genetic resources evaluated for disease resistance

Abstract: Pome fruit genetic resources collections constitute a highly valuable resource not only for fruit breeding but also for direct use by nurseries, growers, and home gardeners. In order to use these resources efficiently and sustainably, reliable evaluation data on fruit and tree characteristics must be generated. Here we focus on pome fruit genetic resources evaluated phenotypically and genotypically for susceptibility to apple scab (Venturia inaequalis), powdery mildew (Podosphaera leucotricha), fire blight (Er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 24 publications
2
22
0
1
Order By: Relevance
“…The incidence and spread of the disease was higher during more humid growth periods (Rancane et al, 2012). Like in other studies (Kellerhals et al, 2012) completely resistant cultivars were not found among the tested ones, but susceptibility was variable (Lâce and Bankina, 2013). This study also discovered dependence of disease severity on the tree location in the orchard.…”
Section: European Pear Rust In Latviamentioning
confidence: 74%
See 2 more Smart Citations
“…The incidence and spread of the disease was higher during more humid growth periods (Rancane et al, 2012). Like in other studies (Kellerhals et al, 2012) completely resistant cultivars were not found among the tested ones, but susceptibility was variable (Lâce and Bankina, 2013). This study also discovered dependence of disease severity on the tree location in the orchard.…”
Section: European Pear Rust In Latviamentioning
confidence: 74%
“…in Crimea cultivars 'Fondante des Bois' and 'Beurre Bosc' were highly susceptible, but the cultivar 'Clapp's Favourite' -less susceptible (Mitrofanova, 1970). In the Netherlands during 60 pear cultivar screening for resistance to certain fungal diseases, some symptoms of European pear rust were observed only on cultivar 'Erika' (Kemp and van Dieren, 2000), whereas no resistant cultivars were identified during the five-year study in a Belgian cultivar collection (Kellerhals et al, 2012). Resistance of different Pyrus species to European pear rust was studied by Fitzner and Fischer (2005) (Ditmar, 1817), the fungus acquired its current name at the end of the same century (Saccardo, 1880).…”
Section: European Pear Rust Control Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several programs on conservation and evaluation of indigenous apple tree genetic resources have been conducted (van Treuren et al 2010). Only a fraction of these collections is used in a limited way in breeding programs, in which often only a narrow genetic pool of standard commercial cultivars is represented (Kellerhals et al 2012). Such focused selection programs result in a decrease of the apple genetic background diversity (Cornille et al 2012).…”
mentioning
confidence: 99%
“…Noyabrskaya (2 points) ( Table 1). Like in other studies (Kellerhals et al 2012) completely resistant cultivars were not found among the tested ones. It was observed also that severity of disease was dependent on the location of tree.…”
Section: Diseases and Pest Susceptibilitymentioning
confidence: 66%